Approaches to a Hemispheric America in The Rag Doll Plagues. An Interview with Chicano Author Alejandro Morales - Maja Neff (Iberoamericana. América Latina - España - Portugal, 2014)
Interview with the professor of Chicano/Latino Studies at the University of California (Irvine), Alejandro Morales, a true pioneer in Chicano literature and one of the most outstanding, powerful and innovative writers on the Chicano experience.